Engaging Students: Indonesian Traditional Culinary Digital Comic as a Media for Teaching Procedure Texts - Hidayatullah, Nanda; Kuncahyo, Nanda Lintang Utari; Sulaiman, Sulaiman (IJET (Indonesian Journal of English Teaching), 2026)
Digital comics can be considered as learning media that can attract students' attention and communicate educational information effectively in. However, little research discusses digital comics about Indonesian traditional culinary. Therefore, this research aims to create an Indonesian traditional culinary digital comic using Pixton to teach procedure texts. This research adopted the Research and Development (R&D) approach with the development model of Plomp, which comprises three phases: preliminary research, prototyping, and assessment. Validation of the developed media was done with the help of media experts, a content expert, and an English teacher. The practicability of the media was tested by collecting the responses from the students. The results revealed that the developed media received a score of 86% of validity, meaning that the media is highly valid, and the responses of the students were 84%, meaning that the media is highly practical for classroom practice. Therefore, the developed digital comic is recommended as an alternative learning medium for teaching procedure texts.